Mexican Strains of Anaplasma marginale: A First Comparative Genomics and Phylogeographic Analysis - Edgar Dantán-González; Rosa Estela Quiroz-Castañeda; Hugo Aguilar-Díaz; Itzel Amaro-Estrada; Fernando Martínez-Ocampo; Sergio Rodríguez-Camarillo (Pathogens, 2022)
The One Health approach looks after animal welfare and demands constant monitoring of the strains that circulate globally to prevent outbreaks. Anaplasma marginale is the etiologic agent of bovine anaplasmosis and is endemic worldwide. This study aimed to analyze, for the first time, the genetic diversity of seven Mexican strains of A. marginale and their relationship with other strains reported. The main features of A. marginale were obtained by characterizing all 24 genomes reported so far. Genetic diversity and phylogeography were analyzed by characterizing the msp1a gene and 5′-UTR microsatellite sequences and constructing a phylogenetic tree with 540 concatenated genes of the core genome. The Mexican strains show 15 different repeat sequences in six MSP1a structures and have phylogeographic relationships with strains from North America, South America, and Asia, which confirms they are highly variable. Based on our results, we encourage the performance of genome sequencing of A. marginale strains to obtain a high assembly level of molecular markers and the performance of extensive phylogeographic analysis. Undoubtedly, genomic surveillance helps build a picture of how a pathogen changes and evolves in geographical regions. However, we cannot discard the study of relationships pathogens establish with ticks and how they have co-evolved to establish themselves as a successful transmission system.